Description of a second species of Sarax Simon, 1892 (Amblypygi, Charinidae) from China - Xu, Yiting; Yu, Kun; Zhang, Shuyuan; Zuo, Anru; Zhang, Feng (Zootaxa, 2025)
A new species of the whip spider genus Sarax Simon, 1892 from Yunnan Province, China is described: S. yunnan Xu, Yu & Zhang, sp. nov., which is now the second Sarax species known only from China. The systematic position of S. yunnan sp. nov. was tested through phylogenetic analysis based on newly sequenced genes (12S, 16S, 18S, 28S and COI) and datasets of previous studies; like Sarax sinensis Wu et al., 2022, Sarax yunnan sp. nov., belongs to the West Asian Clade of Sarax. Finally, we describe the adult female of Sarax sinensis Wu et al., 2022, including data on its genitalia.